Substitution of Durian Seed Flour and Butterfly Pea Flower Extra in Donuts as Children's Healthy Snack - Muharrammah Isnaini; Reni Agustina Harahap (Universitas Ahmad Dahlan, 2023)
Background: Snacks, of course, cannot be separated from human life, especially for children who are growing up. Technological developments have made local food commodities utilize waste durian seeds and use butterfly pea flowers. Durian seed flour and butterfly pea flower have good nutritional content for children's food. Method: This study is an experimental study with a Completely Randomized Design (CRD) with two treatments. (Treatment A) 170 grams of wheat flour + 30 grams of durian seed flour + butterfly pea flower extract, (Treatment B) 140 grams of wheat flour + 60 grams of durian seed flour + butterfly pea flower extract. The organoleptic test assessment was carried out by 25 untrained panelist subjects who were carried out at the Mandiri College Elementary School, Siombak, Medan Marelan. Results: From the above results we can see that treatment A with the addition of 30 grams of durian seed flour and extra butterfly pea flowers was the most preferred in terms of aroma, texture, color, and taste. The color category has a very fond interest with a value of 4.04, the aroma category has a liking interest with a value of 3.96, the texture category has a very fond interest with a value of 4.08, the taste category has a very like interest with a value of 4.28. Conclusion: Substituting durian seed flour and extra butterfly pea flowers for donuts can be another solution for healthy snacks for elementary school children.